Analysis of Debt and Capital Budgets in the Context of Private Companies - Anjani, Mardhiana Dwi; Wahyuni, Dwi; Maemunah, Azis; Khomisah; Laurenza, Dinar; Fauziah, Dafa (Formosa Journal of Sustainable Research, 2024)
This research centers on an examination from top to bottom of asset creation starting from liabilities and equity in private enterprises, with the fundamental goal of distinguishing the elements influencing the assurance of subsidy source. By delving deeper into how organizations handle the levels of debt and equity, it is believed that they can achieve an ideal level of financial effectiveness. The methodology used in this study is enlightening research employing quantitative techniques, where information is obtained from the financial statements of companies listed on the Indonesia Stock Exchange. The consequences of the investigation indicate that organizations implementing a fair capital structure between liabilities and equity generally exhibit more stable financial execution and more controlled opportunities. The findings derived from this research are that effective management of subsidy resources not only plays a role in maintaining financial solidity but also contributes to the long-term seriousness of the organization